Are Older Adults Unique? Examining Presenting Issues and Changes in Therapy Across the Life Span. (March 2020) - Sabey, Allen K.; Jensen, Jakob; Major, Samuel; Zinbarg, Richard; Pinsof, William
With the urgent need to increase and improve mental health care of the growing population of older adults in the United States, clinical research is warranted to further the knowledge and improve the relevant training for mental health professionals working with older adults. This study drew from two diverse clinical samples of adults ages 18 years to 80 years to examine whether and how initial clinical presentations and changes over time in individual, family-of-origin, and relational measures differed across the life span. Results indicated a variety of linear and curvilinear associations between individual, family-of-origin, and relational measures at intake and age, with some moderation by gender. There were no significant results between the amount of change on those measures and age, indicating that older adults may change in similar fashion to middle-aged and younger adults in psychotherapy. Relevant clinical implications are provided.